2021
DOI: 10.3390/ijms22126438
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of PVDF-Coated PCL-TCP Scaffolds and Pulsed Electromagnetic Field on Osteogenesis

Abstract: Bone exhibits piezoelectric properties. Thus, electrical stimulations such as pulsed electromagnetic fields (PEMFs) and stimuli-responsive piezoelectric properties of scaffolds have been investigated separately to evaluate their efficacy in supporting osteogenesis. However, current understanding of cells responding under the combined influence of PEMF and piezoelectric properties in scaffolds is still lacking. Therefore, in this study, we fabricated piezoelectric scaffolds by functionalization of polycaprolact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Their results showed that both the PVDF scaffold and PVDF/PANI scaffold had improved cell attachment and osteogenic differentiation under EMFs exposure, while the combination of EMFs and PVDF/PANI scaffold had a more significant effect [ 168 ]. Similar results were obtained by Dong et al [ 47 ], and they speculated that the mechanical stimulation resulting from the interplay between EMFs and PVDF-coated PCL-TCP scaffolds contributed to the well cellular response. The prominent effect of a combination of PVDF-based material and EMFs is inspiring and holds promises in the field of BTE.…”
Section: Emfs’ Applications In Assisting Bone Tissue Engineeringsupporting
confidence: 89%
See 1 more Smart Citation
“…Their results showed that both the PVDF scaffold and PVDF/PANI scaffold had improved cell attachment and osteogenic differentiation under EMFs exposure, while the combination of EMFs and PVDF/PANI scaffold had a more significant effect [ 168 ]. Similar results were obtained by Dong et al [ 47 ], and they speculated that the mechanical stimulation resulting from the interplay between EMFs and PVDF-coated PCL-TCP scaffolds contributed to the well cellular response. The prominent effect of a combination of PVDF-based material and EMFs is inspiring and holds promises in the field of BTE.…”
Section: Emfs’ Applications In Assisting Bone Tissue Engineeringsupporting
confidence: 89%
“…Moreover, PEMF amplified the surface potential gradient of titanium implant [ 42 ]. Therefore, cations (mainly Ca 2+ ) and proteins/peptides with positive charges would adhere to the negatively charged surface owing to the electrostatic interaction [ 47 ]. Subsequently, integrin on cell membrane, the main mediator in cell–matrix adhesion, recognizes and binds to cell adhesion-mediated motifs such as arginine-glycine-aspartic acid (RGD), which are embedded in adsorbed proteins [ 48 , 49 ].…”
Section: Biological Effects Of Emfs In Bone Tissue Engineering Applic...mentioning
confidence: 99%
“…Pulsed electromagnetic field (PEMF) is viewed as a safe, noninvasive, and effective physical medicine and is a potential treatment for multiple diseases, including delayed wound healing and OA [ 9 ]. A recent study indicated that PEMF not only provides electrical stimulation piezoelectric scaffolds to transport partial mechanical impulses but also provides other functions of long-instance electrical impulses of cell proliferation and differentiation without partial potential of hydrogen alteration or reactive oxygen species creation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A similar trend was observed for the PCL scaffolds (showing an 11.64% weight loss at day 5 for scaffolds with a 200 μm pore size and a 13.37% weight loss at day 5 for scaffolds with a 500 μm pore size), which exhibited the lowest degradation kinetics. This can be explained by the increase in the surface area exposed to the NaOH that accelerates the hydrolytic degradation and the release into the liquid medium of the ceramic particles previously bonded with the polymeric material [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. Results also indicate that, for the same material composition, bone bricks degrade slower compared with rectangular scaffolds.…”
Section: Resultsmentioning
confidence: 99%